KEPENTINGAN TIONGKOK DI KAWASAN ARKTIK TAHUN 2016-2020 - Achmad Ryan; Umi O Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study intends to analyze China's interests in the Arctic region in 20162020. China as a New Emerging Power country has a high level of need for energy resources, so that China has dependence on countries or regions that have availability. China's involvement in the Arctic region is increasingly gradual in line with China's development as a New Emerging Power. In this study, the authors used library research and qualitative research methods. The analysis in this study uses the level of analysis of the nation state, the concept of national interest, using the theory of geopolitics. The use of this theory is because this study discusses China's active involvement in the Arctic region which has strategic value marked by the involvement of large countries such as the United States and Russia with China's geographical factors causing China to need to establish relations with other countries or become influential in a region. particular, the Arctic Region. In this study using the perspective of Neorealism The results of research from China's interests in the Arctic region are an effort to meet the needs of energy resources, the expansion of the Belt Road Initiative and the Balance of Power efforts to the hegemony of the United States through the joining of China with the Arctic Council. Keyword(s) : Interest, New Strategic Frontier, Belt Road Initiative